Relevansi Teori Akuntansi Donleavy dalam Era Digital: Analisis terhadap Adaptasi Standar Akuntansi di Tengah Transformasi Teknologi - Nanda Chairunnisa; Najra Nabiilah Ajar; Iskandar Muda (Yayasan Haiah Nusratul Islam, 2026)
The development of digital technology has brought fundamental changes to accounting theory and practice. The digital transformation marked by the application of Artificial Intelligence (AI), Machine Learning (ML), and the Internet of Things (IoT) has not only affected accounting information systems but also challenged the relevance and conceptual framework of conventional accounting standards such as IFRS and PSAK. This study aims to examine the relevance of classical accounting theory as described by Donleavy in facing the dynamics of financial reporting digitalization. Using a descriptive qualitative approach through literature study, this study evaluates how AI, ML, and IoT change the concepts of faithful representation, measurement reliability, and decision usefulness in financial reporting. The results show that the application of digital technology strengthens transparency, efficiency, and the value of accounting information, but at the same time poses conceptual challenges to the recognition, measurement, and verification of digital assets and artificial intelligence algorithms. A principles-based standards approach is considered more relevant than rule-based standards in the digital context because it provides flexibility and room for professional judgment regarding data-based transactions and intangible assets.